Pupuk Organik Cair Ampas Kopi terhadap Karakteristik Fisiologi dan Pertumbuhan Kangkung Darat - Djoko Purnomo; Gani Cahyo Handoyo; Muji Rahayu; Alya Sausan Fauziyah (Agrotechnology Research Journal, 2023)
Extended use of synthetic chemical fertilizers may degrade soil quality. As a synthetic chemical fertilizer substitute, organic fertilizer can improve soil quality, produce healthier agricultural products, and be environmentally sustainable. Thus, coffee grounds liquid organic fertilizer may solve this problem. This study examines how liquid organic fertilizer made from coffee grounds affects land kale's physiological and growth characteristics. A fully randomized experimental design with one factor and 11 treatments was used. A control group, NPK-16-16-16 4 g, and Arabica, Robusta, and Liberica coffee were treated with three concentrations (4 mL.L-1, 12 mL.L-1, and 20 mL.L-1). Four replicates were run for each treatment. The investigation found that coffee ground liquid organic fertilizer does not meet Minister of Agriculture Decree 261/KPTS/SR.310/M/4/2019 criteria. Compared to the control group, liquid organic fertilizer made from coffee grounds did not increase land kale growth. Additionally, it did not grow as well as with NPK16-16-16 fertilizer. Coffee grinds liquid organic fertilizer only enhances kale growing on land, promoting sustainable agriculture.